2009
DOI: 10.1084/jem.20080003
|View full text |Cite
|
Sign up to set email alerts
|

Loss of STAT5 causes liver fibrosis and cancer development through increased TGF-β and STAT3 activation

Abstract: The molecular mechanisms underlying the development of hepatocellular carcinoma are not fully understood. Liver-specific signal transducer and activator of transcription (STAT) 5A/B–null mice (STAT5-LKO) were treated with carbon tetrachloride (CCl4), and histological analyses revealed liver fibrosis and tumors. Transforming growth factor (TGF)–β levels and STAT3 activity were elevated in liver tissue from STAT5-LKO mice upon CCl4 treatment. To define the molecular link between STAT5 silencing and TGF-β up-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(127 citation statements)
references
References 55 publications
(63 reference statements)
5
120
2
Order By: Relevance
“…[42][43][44] For example, Fujii et al 45 reported that treatment with CCl 4 for 15 weeks induced liver fibrosis and well-differentiated HCC in male A/J strain mice. Furthermore, Hosui et al 46 reported that chronic injection of CCl 4 for 8 weeks induced HCC in 10% of liver-specific STAT5 knockout mice but not in wild-type mice. The present study shows that after 16-week CCl 4 treatment, no HCC development was found in wild-type mice but approximately 60% of STAT3 HepϪ/Ϫ mice developed multiple surface nodular tumors ( Figure 6).…”
Section: Stat3 Prevents Liver Tumorigenesis In a Model Of CCL 4 -Indumentioning
confidence: 99%
“…[42][43][44] For example, Fujii et al 45 reported that treatment with CCl 4 for 15 weeks induced liver fibrosis and well-differentiated HCC in male A/J strain mice. Furthermore, Hosui et al 46 reported that chronic injection of CCl 4 for 8 weeks induced HCC in 10% of liver-specific STAT5 knockout mice but not in wild-type mice. The present study shows that after 16-week CCl 4 treatment, no HCC development was found in wild-type mice but approximately 60% of STAT3 HepϪ/Ϫ mice developed multiple surface nodular tumors ( Figure 6).…”
Section: Stat3 Prevents Liver Tumorigenesis In a Model Of CCL 4 -Indumentioning
confidence: 99%
“…As STAT3 has been the focus of cancer research, STAT3 inhibitors are being investigated, and a growing number of preclinical studies are ongoing. Therefore, more and more researchers have begun to focus on STAT5 (15)(16)(17)(18)(19). Evidence reveals that inhibition of STAT5 affects biological behavior of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…28 A recent study has suggested that STAT5 might have a crucial role in hepatic tumorigenesis. 29 However, its role in cancer development is still controversial as it might also act as a tumor inducer [30][31][32][33] as well as a tumor suppressor. 29,34 No STAT5 activation was detected in gp130 f/f livers 40 weeks after DEN treatment (Figure 7b, Supplementary Figure 7c).…”
Section: Hcc Initiation In Gp130mentioning
confidence: 99%
“…As STAT5 activation has been shown to trigger tumor growth in a TGFβ-dependent manner, 29 we examined the TGFβ pathway in more detail. We found significantly decreased TGFβ expression in gp130…”
Section: 43mentioning
confidence: 99%